aspect the expression by grouping. First, the expression requirements to be rewritten as 3x^2+ax+bx+8. To discover a and b, collection up a device to be solved.

You are watching: Factor 3x^2-2x-8


Since abdominal is positive, a and b have actually the exact same sign. Since a+b is negative, a and b are both negative. List all such integer bag that give product 24.
*

3x2-10x+8 Final an outcome : (x - 2) • (3x - 4) action by step solution : step 1 :Equation at the end of step 1 : (3x2 - 10x) + 8 action 2 :Trying to aspect by separating the center term ...
you can constantly use the basic formula for a quadratic equation, if we have actually ax^2+bx+c then let x_1=frac-b+sqrtb^2-4ac2a and x_2=frac-b-sqrtb^2-4ac2a then we deserve to write ax^2+bx+c=a(x-x_1)(x-x_2) ...
displaystyle=left(left(3x-7 ight)left(x-1 ight) ight. Explanation: displaystyle3x^2-10x+7 us can separation the center Term the this expression to factorise ...
3x2-10x+8=0 Two options were found : x = 4/3 = 1.333 x = 2 step by step solution : action 1 :Equation at the end of step 1 : (3x2 - 10x) + 8 = 0 action 2 :Trying to aspect by dividing the ...
x2-10x+8=0 Two remedies were uncovered : x =(10-√68)/2=5-√ 17 = 0.877 x =(10+√68)/2=5+√ 17 = 9.123 step by step solution : action 1 :Trying to aspect by splitting the middle term ...
3x2+10x+8 Final an outcome : (3x + 4) • (x + 2) step by action solution : action 1 :Equation in ~ the finish of action 1 : (3x2 + 10x) + 8 step 2 :Trying to element by separating the middle term ...
More Items
*
*

*
*
*

Factor the expression through grouping. First, the expression demands to it is in rewritten together 3x^2+ax+bx+8. To find a and b, set up a mechanism to it is in solved.
Since abdominal is positive, a and also b have the very same sign. Because a+b is negative, a and also b are both negative. List all together integer bag that give product 24.
Quadratic polynomial deserve to be factored making use of the transformation ax^2+bx+c=aleft(x-x_1 ight)left(x-x_2 ight), whereby x_1 and also x_2 room the remedies of the quadratic equation ax^2+bx+c=0.
All equations the the kind ax^2+bx+c=0 deserve to be fixed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula provides two solutions, one when ± is addition and one as soon as it is subtraction.
Factor the original expression utilizing ax^2+bx+c=aleft(x-x_1 ight)left(x-x_2 ight). Substitute 2 for x_1 and frac43 for x_2.

See more: How Many Calories In Fried Dough Bread, Bread, Fried, Dough Nutrition Facts And Analysis


Subtract frac43 indigenous x by finding a usual denominator and subtracting the numerators. Then reduce the fraction to lowest state if possible.
*
*